In vitro production of steroidal saponin, total phenols and antioxidant activity in callus suspension culture of Paris polyphylla Smith: an important Himalayan medicinal plant - Rawat, Janhvi Mishra; Pandey, Shweta; Rawat, Balwant; Purohit, Sumit; Anand, Jigisha; Negi, Arvind S.; Thakur, Ajay; Mahmoud, Mohamed H.; El-Gazzar, Ahmed M.; El-Saber Batiha, Gaber (Frontiers in Plant Science, 2023)
Paris polyphylla Smith (Melanthiaceae) family, which is native to the Himalayan region, has received a lot of attention recently due to its extensive history of usage in traditional medicine. The production of steroidal saponin from callus suspension cultures of P. polyphylla was observed in the current study. A light-yellow callus was formed within six weeks of cultivating rhizomes on Murashige and Skoog (MS) media supplemented with Thidiazuron (TDZ). Furthermore, the effect of TDZ, Methyl Jasmonate (MeJA), and Yeast Extract (YE) on callus growth, steroidal saponin (dioscin and diosgenin), total phenolic content, total flavonoids, total tannin, and total antioxidant activity was also measured. The medium containing 0.5 µM TDZ depicted the maximum callus biomass (2.98 g fresh weight). Significantly high phenolic and tannin content was observed in the MS medium containing 50 µM MeJA, whereas, no significant increase was observed in total tannin production in any treatment. Three in vitro assays, DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS (2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)) and FRAP (ferric ion reducing antioxidant potential) and FC (Folin-Ciocalteu), were used to assess antioxidant potential of callus. Maximum antioxidant analysis reported in 1.0 µM TDZ (6.89 mM AAE/100 g) containing medium followed by 50 µM MeJA (6.44 mM AAE/100 g). The HPLC analysis showed a high presence of dioscin and diosgenin (5.43% and 21.09%, respectively) compared to the wild sample (2.56% and 15.05%, respectively). According to the results, callus produced on media supplemented with 50 µM MeJA have significant phenolic contents and elevated antioxidant activity; nevertheless, callus growth was greater in the presence of 0.5 µM TDZ. The findings of the current study have commercial implications since greater biomass production will result in active phytochemicals that the pharmaceutical and nutraceutical sectors are in need desperately.